Síntese e caracterização de hidrogéis de poli [(N-Isopropilacrilamida)-CO-(Ácido metacrílico)] e sua aplicação como sistemas de liberação controlada de medicamentos - Fabio Peixoto Silva (2006)
The present work general objective was the study of the feasibility of producing biodiesel from defective coffee beans, as an alternative for removing those defective beans from the international market. Soybean oil and coffee oil from both defective and healthy beans were used to produce biodiesel. Coffee oils were obtained by solvent (hexane) extraction in an industrial Soxhlet apparatus with an extraction capacity of 20 kg of beans per batch. The soybean oil was acquired from local markets. All oils had it acidity determined. The transesterification reactions were performed in a stirred reactor, heated by a hot waterjacket. The temperature of the water in the jacket was controlled by a thermostatic water bath. Two alcohols were employed, methanol and ethanol, in the presence of both basic (sodium methoxide) and acid (sulfuric acid) catalysts. Biodiesel samples produced wereanalyzed by gas chromatography in order to determine reaction conversion. Density, viscosity and heat of combustion of the biodiesel produced were also determined. Coffee oil from defective beans presented the greatest acidity. Reactions performed with oil fromhealthy coffee beans in the presence of basic catalyst presented complete phase separation at the end of the reaction. The product of the transesterification reaction using oil from defective coffee beans gelified completely due to large amounts of free fatty acids present in the oil. Phase separation in reaction product using acid catalyst was observed only for soybean oil. Removing excess alcohol from product reactions for both healthy coffee bean oil and defective coffee bean oil resulted in complete sample gelification. However, phase separation was observed after treating samples with acid. Biodiesel samples produced withsoybean oil presented the greatest yields. The presence of impurities and free fatty acids in both coffee oils explain such difference in yields. Viscosity reduction was observed for all samples after transesterification. Samples produced from healthy coffe bean oil and soybean oil showed reduction in density and those produced using defective coffee bean oilpresented an increase in viscosity. Heat of combustion increased for biodiesel produced from soybean oil and defective coffee oil when compared to crude oil. Heat of combustion for biodiesel from healthy coffee oil was similar to that of the crude oil. Differences in the nature of impurities present in both coffee oils can explain such behavior. Allcharacteristics determined for biodiesel samples attended Europeans standards. When compared to Diesel No.2 fuel, all samples presented greater density and viscosity and lower heat of combustion. Regarding the results obtained in this work it is possible to conclude that the production of biodiesel from defective coffee beans is feasible.